Road Traffic Accidents in Kathmandu Valley - Dhakal, Krishna Prasad (Journal of Health Promotion, 2018)
This article presents the information received from documents available in the Police Head- Quarters, Operation Department, Traffic Directorate, Naxal, Kathmandu and Metropolitan Traffic Police Division, Kathmandu along with some journals and websites covering five years from 2069 to 2074. The main aim of carrying out this research was to shed light on the road traffic accidents of Kathmandu valley. The data have been presented through document analysis and analyzed here using both quantitative and qualitative techniques. The major findings include that Road Traffic Accidents are the outcomes of many factors ranging from the negligence of the driver to the weather condition and the condition of road. Despite the dense presence of government and its bodies, the study showed that maximum number of road traffic accidents occur in Kathmandu valley. Youngsters riding bikes and driving cars involved in accident are found maximum in number. Because of the immediate rescue and hospitalization, the number of deaths in Kathmandu valley was found to be decreasing in comparison to the other parts of Nepal. Journal of Health Promotion Vol.6 2008, p.37-44